PELAKSANAAN SUPERVISI KLINIS UNTUK MENINGKATAN KINERJA GURU MATA PELAJARAN YANG DIUJIKAN DALAM UJIAN NASIONAL SMP DI KECAMATAN BANTUL KABUPATEN BANTUL (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The purpose of the research is to explain the implementation of clinical supervision by a supervisor. Planning, implementing, and evaluating for subject teachers that be tested in the national examination in SMP Bantul Subdistrict, Bantul Regency. The clinical supervision can improve the capability of work for subject teachers that be tested in the national examination in Bantul Subdistrict, Bantul Regency. This research is a kind of qualitative descriptive research. It is located in SMP in Bantul Subdistrict, Bantul Regency. The data are obtained from two resources . they are in the field and documents. The result of this research show of clinical supervision, it can improve the capability of work for subject teachers that be tested in the national examination for SMP degree in Bantul subdistrict, Bantul Regency. It can be knew from (1) the implementation for clinical supervision in SMPN Bantul Subdistrict, Bantul Regency had been suitable for the procedure planning, implementing, and evaluation phases, (2)The implementation of clinical supervision has a role in learning process, in fact the teachers have been able to make or arrange a lesson plan, to use and benefit the learning media, etc, (3) there are some obstacles with related by implementing clinical supervision.